Comparative Study of Adsorption of Methylene Blue and Basic Red 9 Using Rice Husks of Different Origins - Hadid Sukmana; Etelka Tombácz; Gergő Ballai; Gábor Kozma; Zoltán Kónya; Cecilia Hodúr (Recycling, 2023)
Methylene blue (MB) and basic red 9 (BR9) are cationic dyes that are commonly used in the dye industry and negatively affect humans and other living organisms. This study compares the performance of Indonesian rice husk (IRH) and Hungarian rice husk (HRH) as bio-adsorbents for removing MB and BR9 from aqueous solutions. Chemical content, zeta potential, and Fourier-transform infrared spectroscopy analyses were used to characterize the rice husks (RHs). Adsorption studies were performed through batch experiments involving several parameters, namely, pH, adsorbent dose, initial dye concentration, contact time, and temperature to observe the self-association (aggregation) of MB and BR9. Adsorption kinetic studies showed that maximum dye removal was achieved at a contact time of 120 min. MB and BR9 adsorption followed a pseudo-second order kinetic model, and the BET multilayer isotherm model provided a better fit to the experimental data of MB and BR9 adsorption. The IRH adsorption capacities were 15.0 mg/g for MB and 7.2 mg/g for BR9, whereas those of HRH were 24.4 mg/g for MB and 8.3 mg/g for BR9. Therefore, these RHs are potential bio-adsorbents for removing MB and BR9 from aqueous solutions.